Financial Economics A Concise Introduction to Classical and Behavioral Finance - Hens, Thorsten; Rieger, Marc Oliver; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Financial economics is a fascinating topic where ideas from economics, mathematics and, most recently, psychology are combined to understand financial markets. This book gives a concise introduction into this field and includes for the first time recent results from behavioral finance that help to understand many puzzles in traditional finance. The book is tailor made for master and PhD students and includes tests and exercises that enable the students to keep track of their progress. Parts of the book can also be used on a bachelor level. Researchers will find it particularly useful as a source for recent results in behavioral finance and decision theory. "By mixing rigour and humour, Hens and Rieger make learning financial economics fun. The book is nicely organized into three logical parts. Most importantly, the discussion features a smooth transition from the classical approach to the behavioural approach, helping students fill in the metaphorical jig saw puzzle representing the corpus of finance theory." Hersh Shefrin, finance professor at the Santa Clara University, USA, and author of "Beyond Greed and Fear" and "A Behavioral Approach to Asset Pricing Theory This textbook provides a modern treatment of the theory of financial economics. It stands out by fully integrating the classical and the behavioral approach in a lucent, yet rigorous way. I highly recommend it! Markus K. Brunnermeier, Princeton University Behavioral economics, decision theory and the equilibrium analysis of financial markets have largely evolved as separate parts of the landscape of modern economics: in this ambitious book the authors present a common framework for uniting these separate subfields. (3z(BFinancial Economics(3y (Bby Hens and Rieger is a delight to read, striking for its clarity, for the breadth of topics covered and for the wealth of well-chosen examples that illustrate the key ideas. Michael Magill Martine Quinzii University of Southern California University of California, Daviss
Foundations -- Decision Theory -- Financial Markets -- Two-Period Model: Mean-Variance Approach -- Two-Period Model: State-Preference Approach -- Multiple-Periods Model -- Advanced Topics -- Theory of the Firm -- Information Asymmetries on Financial Markets -- Time-Continuous Model.
Keywords: Economics; Finance; Banks and banking; Economics/Management Science; Financial Economics; Finance /Banking.; Quantitative Finance; Economic Theory